EFFECTIVENESS OF THE LEBED METHOD THERAPEUTIC INTERVENTION ON PHYSICAL STABILITY AMONG ELDERLY INDIVIDUALS IN KAKAMEGA COUNTY - Micky Olutende Oloo; Edwin Kadima Wamukoya; James Aggrey Oloo (Scientific Publishing House. NSA Press, 2024)
Background. In Kenya, falls among individuals over 60 years of age are a major concern. Despite physical activity being known to reduce fall risks, existing studies face challenges like high drop-out rates and limited exercise types. The Lebed Method, a dance program originally developed for breast cancer survivors by Sherry Lebed Davis, has shown potential to improve physical and emotional well-being. This study aimed to explore its effectiveness in improving physical stability among the elderly in Kakamega County. Methods. The study involved a community-based randomized control trial with 30 participants aged 60 and older, selected based on low social support scores. They were divided into intervention and control groups, meeting specific inclusion criteria. Baseline functional stability (mobility and balance) was assessed by Timed Up and Go (TUG), Berg Balance Scale (BBS) scores, gait speed time, and de Morton Mobility Index (DEMMI) score. To ensure the reliability of the study, biases such as selection, performance, detection, attrition, and reporting biases were addressed. Changes in physical stability between the groups were analyzed using the Analysis of Covariance, accounting for baseline differences, while within-group changes were evaluated using the dependent sample t-test. The threshold for statistical significance was set at p < 0.05. Results. The findings showed that the intervention group improved significantly in physical stability compared to the control group. Specifically, notable enhancements were observed on TUG times (p < .001, ηp2 = 0.53, d = 3.38), BBS scores (p < .001, ηp2 = 0.64, d = 1.97), gait speed (p < .001, ηp2 = 0.65, d = 1.99) and DEMMI score (p < .001, ηp2 = 0.38, d = 1.94). Conclusions. The intervention significantly improved mobility and balance among participants, demonstrating the effectiveness of the Lebed method for elderly individuals. Future research could explore specific components of dance-based therapy that contribute to functional mobility and balance improvements.